Pengaruh Waktu Fermentasi Teh Kombucha Kadar 50% Terhadap Tebal Dinding Dan Diameter Lumen Arteria Koronaria Tikus Putih - Isdadiyanto, Sri (Bioma : Berkala Ilmiah Biologi, 2018)
The objective of this study was to analyze the influences of 50% kombucha tea level on wall thickness and lumen diameter of coronary artery in rats. Sixteen male Rattus norvegicus rats, 2 months of age were used as experimental animals, with treatment kombucha tea that has been fermented for 6, 9 and 12 days at the temperature of 25oC per oral. The research design used to a completely randomized with 4 treatment (for 4 weeks) and 4 replications, i.e., P0 = control, without of kombucha tea, P1 = water + 1,8 ml kombucha tea that has been fermented for 6 days in the morning and afternoon, P2 = water + 1,8 ml kombucha tea that has been fermented for 9 days in morning and afternoon, P3 = water + 1,8 ml kombucha tea that has been fermented for 12 days in morning and afternoon. Variables measured were wall thickness and lumen diameter of coronary artery. Data were analyzed with ANOVA followed by Duncan test at 95% confidence level were performed using SPSS version 10,0. The result showed that kombucha tea did not influences the wall thickness and lumen diameter of coronary artery in rats. Key words: Rattus norvegicus, 50% kombucha tea level, wall thickness, lumen diameter, coronary artery